Valuing vacancies : Temporal productive revitalisation of neglected land - Wood, Michael (School of Architecture, Planning and Geomatics, 2017)
Neglected or underutilised spaces in cities have never been as important as they are today as land is consumed by rapid urbanisation. Landscape architects have been transforming these sites into public places, an example being the repurposing of a disused rai l line to create the High Line in New York, testimony to the inherit opportunity that brownfield sites possess. However, these projects require a significant capital injection making them unsuitable for the South African context. This presents an opportunity for an alternative landscape revitalisation model. This project will endeavour to create a new landscape architectural model to utilise temporary vacant sites within the urban realm- sites with high land value. This model is based around productive landscapes for growing food and has the potential to address some key challenges that cities face, including but not limited to recreational deficits, limited job opportunities and limited education regarding the production of food. The project draws inspiration from the unrestrained beauty of the weedscapes that have colonised derelict sites within the foreshore for the past 79 years and been responsible for the transformation of dredged beach sand into fertile soils, rich in opportunity for temporal productivity. The currently vacant site is located within the reclaimed foreshore of Cape Town's CBD and will act as a pilot site for further initiatives within the city. The abundance of vacant land parcels adjacent to the Port of Cape Town has the ability to provide temporary productive landscapes and initiate new pedestrian linkages to the Waterfront precinct. The project utilises a methodology that begins with detailed transects showing existing relationships between plant communities and the material and soils of the derelict site. It additionally uses the inherit seasonal aesthetic potential that weeds possess, merging it with productive planting compositions· a methodology utilised by Piet Oudolf.